2019
DOI: 10.21273/hortsci14067-19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-Benzyladenine, γ-Aminobutyric Acid, and Nitric Oxide on Plant Growth, Photochemical Efficiency, and Ion Accumulation of Perennial Ryegrass Cultivars to Salinity Stress

Abstract: Plant growth regulators (PGRs) can mediate plant response to salinity stress. Perennial ryegrass (Lolium perenne) cultivars of BrightStar SLT, Catalina, Inspire, and SR4660ST were exposed to 0, 100, or 200 mm NaCl for 14 d. 6-benzyladenine (6-BA, 10 µm), γ-aminobutyric acid (GABA, 500 µm), nitric oxide (NO, 200 µm), and H2O were applied to the foliage every day for 3 days before s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In response to NO, CAT activity showed a gradual increase over time [40]. Ji et al [41] Sprayed NO donors on the leaves of cotton to increase the biosynthesis of the CAT gene in cotton under normal growth conditions and thereby increase CAT activity, consistent with the results of this experiment. To sum up, spraying SNP increased the activity of antioxidant enzymes in soybean and enhanced the ability of soybean to cope with drought stress.…”
Section: Discussionsupporting
confidence: 82%
“…In response to NO, CAT activity showed a gradual increase over time [40]. Ji et al [41] Sprayed NO donors on the leaves of cotton to increase the biosynthesis of the CAT gene in cotton under normal growth conditions and thereby increase CAT activity, consistent with the results of this experiment. To sum up, spraying SNP increased the activity of antioxidant enzymes in soybean and enhanced the ability of soybean to cope with drought stress.…”
Section: Discussionsupporting
confidence: 82%
“…A previous report showed that CK and NO regulated the salt tolerance of perennial ryegrass by reducing Na + accumulation and improving growth and photochemical efficiency [ 90 ]. Other researchers demonstrated that the foliar application of SNP increased the expression of CK biosynthesis genes (e.g., ZR , IPA , and IPT1 ) in cotton, suggesting that NO promotes CK biosynthesis, which delays salt-induced leaf senescence [ 91 ].…”
Section: No Signaling Under Conditions Of Salt Stressmentioning
confidence: 99%
“…Thus, supplemental 6-BA allows plants to overcome the negative effects of various types of abiotic stress. Treatment with 6-BA has been shown to enhance photochemical efficiency, increase growth, and reduce Na + accumulation in ryegrass in a saline environment; thus effectively preventing the inhibition of growth in plants experiencing salt stress (Ji et al, 2019). The exogenous application of 6-BA could significantly reduce toxicity caused by cadmium (Cd) and uranium (U) on rapeseed, subsequently reducing malondialdehyde (MDA) and H 2 O 2 levels and increasing antioxidant levels (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, no study has investigated the role of 6-BA-induced tolerance to waterlogging stress in waxy corn. Based on previous studies, which have explored the role of 6-BA in other plants undergoing different forms of stress (Ji et al, 2019;Chen et al, 2020;Hu et al, 2020;Li et al, 2020;Wang X. Y. et al, 2020), we hypothesized that 6-BA scavenges ROS by the promotion of the AsA-GSH cycle system and alleviates the adverse effects of oxidative damage from waterlogging stress in waxy corn seedlings, thereby enhancing tolerance to waterlogging in waxy corn seedlings. Hence, the effect of leaf-sprayed 6-BA in two genotypes of waxy corn seedlings when waterlogged was investigated by comparing morphology, ROS metabolism, cell stability, and the AsA-GSH cycle to verify whether 6-BA prevents oxidative damage from waterlogging stress in waxy corn seedlings.…”
Section: Introductionmentioning
confidence: 99%